2013
DOI: 10.1186/1472-6882-13-7
|View full text |Cite
|
Sign up to set email alerts
|

Murraya koenigii leaf extract inhibits proteasome activity and induces cell death in breast cancer cells

Abstract: BackgroundInhibition of the proteolytic activity of 26S proteasome, the protein-degrading machine, is now considered a novel and promising approach for cancer therapy. Interestingly, proteasome inhibitors have been demonstrated to selectively kill cancer cells and also enhance the sensitivity of tumor cells to chemotherapeutic agents. Recently, polyphenols/flavonoids have been reported to inhibit proteasome activity. Murraya koenigii Spreng, a medicinally important herb of Indian origin, has been used for cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 37 publications
3
38
0
Order By: Relevance
“…In particular, the 26S protease regulatory subunit 10B is a protein associated with apoptosis, and disappears in the floating cells. The decreased activity of the 26S proteasome and induction of cell death was observed only in breast cancer cells and not in normal cells, treated with Murraya koenigii leaf extract (37). The western blot of the present study also demonstrated that expression of hnRNP H and hnRNP A2/B1 disappeared completely subsequent to apigenin treatment.…”
Section: Discussionsupporting
confidence: 52%
“…In particular, the 26S protease regulatory subunit 10B is a protein associated with apoptosis, and disappears in the floating cells. The decreased activity of the 26S proteasome and induction of cell death was observed only in breast cancer cells and not in normal cells, treated with Murraya koenigii leaf extract (37). The western blot of the present study also demonstrated that expression of hnRNP H and hnRNP A2/B1 disappeared completely subsequent to apigenin treatment.…”
Section: Discussionsupporting
confidence: 52%
“…Increased activation in the DPPH assay from the optimized extracts corroborates these earlier findings. The anticancer activity of curry leaf extracts against MDA-MB-231 and MCF-7 cell lines (breast cancer) has been reported previously [15, 29, 30]. The anticancer activity of curry leaves against HeLa cancer cells and the effective dose of this extract have been scarcely reported.…”
Section: Resultsmentioning
confidence: 99%
“…Murraya koenigii leaves to be a potent source of proteasome inhibitors that lead to cancer cell death. The active component(s) such as koenidine from the leaf extract might be playing role in the reducing the proliferation rate of the cells [39]. When we tested the KND on human brain cells, the similar kind of effects such as a significant reduction on cell proliferation was observed.…”
Section: Discussionmentioning
confidence: 54%